Pregnancy outcome in women before and after cervical conisation: population based cohort study. (18th September 2008) - Albrechtsen, Susanne; Rasmussen, Svein; Thoresen, Steinar; Irgens, Lorentz M; Iversen, Ole Erik
Abstract : Objectives To examine the consequences of cervical conisation in terms of adverse outcome in subsequent pregnancies. Design Population based cohort study. Data sources Data on cervical conisation derived from the Cancer Registry of Norway and on pregnancy outcome from the Medical Birth Registry of Norway, 1967-2003. 15 108 births occurred in women who had previously undergone cervical conisation and 57 136 who subsequently underwent cervical conisation. In the same period there were 2 164 006 births to women who had not undergone relevant treatment (control). Results The proportion of preterm delivery was 17.2% in women who gave birth after cervical conisation versus 6.7% in women who gave birth before cervical conisation and 6.2% in women who had not undergone cervical conisation. The relative risk of a late abortion (<24 weeks' gestation) was 4.0 (95% confidence interval 3.3 to 4.8) in women who gave birth after cervical conisation compared with no cervical conisation. The relative risk of delivery was 4.4 (3.8 to 5.0) at 24-27 weeks, 3.4 (3.1 to 3.7) at 28-32 weeks, and 2.5 (2.4 to 2.6) at 33-36 weeks. The relative risk of preterm delivery declined during the study period and especially of delivery before 28 weeks' gestation. Conclusion Cervical conisation influences outcome in subsequent pregnancies in terms of an increased risk of preterm delivery, especially in the early gestational age groups in which the clinical significance is highest. A careful clinical approach should be taken in the selection of women for cervical conisation and in the clinical care of pregnancies after a cervical conisation.